Herpes Simplex Virus Type 1 Propagation, Titration and Single-step Growth Curves - Grosche, Linda; Döhner, Katinka; Düthorn, Alexandra; Hickford-Martinez, Ana; Steinkasserer, Alexander; Sodeik, Beate (Bio-protocol, 2019)
Given the endemic seroprevalence of herpes simplex viruses (HSV), its associated human diseases, and the emergence of acyclovir-resistant strains, there is a continuous need for better antiviral therapies. Towards this aim, identifying mechanistic details of how HSV-1 manipulates infected cells, how it modulates the immune responses, and how it causes diseases are essential. Measuring titers and growth kinetics of clinical isolates and viral mutants are important for a thorough characterization of viral phenotypes in vitro and in vivo. We provide protocols for the preparation as well as titration of HSV-1 stocks, and explain how to perform single-step growth curves to characterize the functions of viral proteins or host factors during infection. In particular, we describe methods to prepare and characterize high-titer HSV-1 stocks with low genome to titer ratios that are required for infection studies in cell culture and animal experiments.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Herpes simplex virus type 1; Plaque assay; Single-step growth curve; Virus propagation